Synthesis of ZnO/CaO Catalyst from Eggshell Waste for Biodiesel Production - Wicaksono, Dino; Kusumaningtyas, Ratna Dewi (Universitas Negeri Semarang, 2019)
The diminishing of fossil fuel reserve has raised a consideration on the renewable energy development. Biodiesel is among the promising renewable energy which is feasible for large-scale production. Biodiesel is generally synthesized through the alkaline-catalyst transesterification of vegetable oil. The common catalyst for biodiesel is homogeneous base catalysts which are active but show several drawbacks related to the environmental aspects. Therefore, development of heterogeneous alkaline catalyst for biodiesel production is critical. CaO catalyst is considered a favourable heterogeneous base catalyst for transesterification reaction and it can be derived from various natural resources. In this work, CaO catalyst from eggshell was synthesized from eggshell waste. To improve the catalyst activity, CaO was combined with ZnO active metal, resulting ZnO/CaO catalyst. In this research, the development, characterization, and application of ZnO/CaO catalyst for waste cooking oil (WCO) transesterification to produce biodiesel has been investigated. Various concentration of ZnO was combined with CaO to determine the best formulation of ZnO/CaO catalyst development. It was demonstrated that the addition of ZnO active metal on CaO catalyst could remarkably improve the biodiesel yield through WCO transesterification reaction. The addition of 6% ZnO active metal on CaO, forming ZnO/CaO 6% catalyst, has exhibited the optimal enhancement of biodiesel yield. Furthermore, it was found that the optimum amount of ZnO/CaO 6% catalyst added in the reaction system was 3% w/w catalyst/WCO.